METODE EKSPLORASI TERHADAP KEMAMPUAN MENGGAMBAR ANAK - Cahyani, Larasati Wahyu; Mashar, Riana; Hermahayu, Hermahayu (Universitas Muhammadiyah Magelang, 2014)
This study was aimed to find out the influence of exploration learning method on drawing ability of students of ?Aisyiyah Kindergarten Group B of Pituruh, Purworejo Regency. The study employed quasi-experimental design. The samples were 20 children for experimental group and 20 children for control group. It used purposive sampling technique. Observation sheet and performance assessment sheets were administered as the instruments of data collection refering to the performance indicators. The 10 performance assessments were considered to be valid and reliable. The data were analyzed using Kolmogorov Smirov test using SPSS Version 16.0 for testing normality. Average scores of the drawing ability were 2.2 at the beginning and increased to 3.5. Hypothesis was tested using paired-sample t test. T value and the probability were 1.001<0.005. In view of findings, it was concluded that exploration learning method influenced students? drawing ability.